Development of Shape Memory and Superelasticity in Binary TiNi-Based Alloys under Torsion of Samples with B19 Structure; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Zhapova D. Dorzhima; Grishkov V. Victor; Lotkov A. Aleksander; Timkin V. Victor; Gusarenko A. Angelina (2018, 2018)
Title screen